2019
DOI: 10.1038/s41598-019-40830-0
|View full text |Cite
|
Sign up to set email alerts
|

Metatranscriptomic evidence for classical and RuBisCO-mediated CO2 reduction to methane facilitated by direct interspecies electron transfer in a methanogenic system

Abstract: In a staged anaerobic fluidized-bed ceramic membrane bioreactor, metagenomic and metatranscriptomic analyses were performed to decipher the microbial interactions on the granular activated carbon. Metagenome bins, representing the predominating microbes in the bioreactor: syntrophic propionate-oxidizing bacteria (SPOB), acetoclastic Methanothrix concilii, and exoelectrogenic Geobacter lovleyi, were successfully recovered for the reconstruction and analysis of metabolic pathways involved in the transformation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 31 publications
(40 reference statements)
3
19
0
Order By: Relevance
“…4), indicate that the acetoclastic pathway mainly works for methanogenesis in the presence of MNPs under continuous agitation. In previous studies, metatranscriptomic analyses have demonstrated that genes coding for hydrogenotrophic methanogenesis pathways are upregulated in methanogens in association with the occurrence of Geobacter, and these data are considered to support the idea that DIET is involved in methanogenesis (17,18). In contrast, the metatranscriptomic data reported here suggest that MNPs stimulate acetoclastic methanogenesis, and we therefore conclude that MNPs did not promote DIET in agitated cultures.…”
Section: Resultssupporting
confidence: 72%
“…4), indicate that the acetoclastic pathway mainly works for methanogenesis in the presence of MNPs under continuous agitation. In previous studies, metatranscriptomic analyses have demonstrated that genes coding for hydrogenotrophic methanogenesis pathways are upregulated in methanogens in association with the occurrence of Geobacter, and these data are considered to support the idea that DIET is involved in methanogenesis (17,18). In contrast, the metatranscriptomic data reported here suggest that MNPs stimulate acetoclastic methanogenesis, and we therefore conclude that MNPs did not promote DIET in agitated cultures.…”
Section: Resultssupporting
confidence: 72%
“…Methanofastidiosales was absent in both bulk liquid and GAC, but was present on ABS (4.4%). These observations collectively suggest that biofilm and bulk communities in AFMBR are distinct from each other, corroborating with previous studies [ 59 , 60 ]. Collectively, biocarrier material is also a determining factor in how the microbial community is shaped.…”
Section: Resultssupporting
confidence: 92%
“…Moreover, Geobacter can consume acetate and extracellularly release electrons that are used by Methanothrix via direct interspecies electron transfer (DIET) [ 62 ]. Under such circumstances, Methanothrix could utilize CO 2 as the carbon source for methanogenesis, which would otherwise be impossible without its exoelectrongenic partner [ 60 ]. Although bulk liquid also contains Geobacter (1.3%), the currently known mechanisms of DIET requires proximity to function and is unlikely to occur in the suspension of liquid [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Metatranscriptomics have recently been used in combination with metagenomics to analysis MBR microbial community dynamics and interactions (Yang et al, 2019). However, these methods are still in their infancy and only a few studies have applied them in the context of MBR, making it hard to source sufficient literature for a thorough review.…”
Section: Microbial Community Analysismentioning
confidence: 99%